Does High Volume of Exercise Training Increase Aseptic Vascular Inflammation in Male Athletes?. Issue 3 (June 2019) - Zembron-Lacny, Agnieszka; Tylutka, Anna; Zeromska, Agnieszka; Kasperska, Anna; Wolny-Rokicka, Edyta
Aseptic vascular inflammation can be caused by high levels of various inflammatory and apoptotic factors such as tumor necrosis factor (TNFα), nitric oxide (NO), 3-nitrotyrosine (3-Nitro), and free and oxidized low-density lipoproteins (oxLDL) generated during intense exercise. Endothelial dysfunction resulting from enhanced inflammation has been implicated in cardiovascular disease (CVD). The purpose of the study was to observe the effects of high volume of exercise training on inflammatory mediators and their interaction with conventional CVD risk factors. Blood samples were collected from highly-trained men ( n = 16, 21.8 ± 4.0 years) as well as from nonactive men ( n = 20, 21.1 ± 1.1 years). NO concentration did not differ between groups while TNFα, 3-Nitro, oxLDL, and CRP levels were significantly higher in athletes compared to nonathletes. TNFα reached even 7-fold higher level in athletes and was highly correlated with CVD risk factor such as TG, lipoproteins LDL and HDL as well as CRP. Approximately 50% of physically active men demonstrated a 20% increase in non-HDL caused by high levels of TC and LDL. These findings suggest that athletes with a high exercise volume demonstrate increased levels of circulating biomarkers of vascular inflammation and may be more likely to have CVD.